PENGARUH PENGGUNAAN VARIASI METODE DAN MODEL PEMBELAJARAN TERHADAP HASIL BELAJAR FISIKA SISWA KELAS VIII SMPN2 MARGATIGA SEMESTER GENAP TP 2013/2014 - Fitriani, Eni; Mulyani, HRA (Jurnal Pendidikan Fisika, 2015)
The purpose of this study was to investigate the effect of variations in the methods and models of teaching to student learning outcomes VIII SMPN2 MARGA TIGA.This research is experimental research which ofdesign completely randomized or completely randomized experimental design.The population in thisresearch is all of student VIII class in SMPN 2 MARGA TIGA2013/2014. The sample in this research is VIIIth class which totaling 34 students.In this research, conducted with three treatments of learning in a classroom.Data collection techniques in this research use the technique of the test, which tests the end (posttest) were then analyzed with the test results hipotesis. From posttest analysis results of hypothesis testing using one-way ANOVA test (Completely Randomized Design) at the 5% significance level value obtained results Fobs = 1.5244 and Ftab = 3.10 this shows that H0 is accepted and means variety of methods and learning models provide a similar impact on student learning outcomes.It can be concluded that all three treatments had similar quality if tailored to the needs of all three materials.Â